2018
DOI: 10.1177/1687814018772404
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation for three-dimensional rotor icing in forward flight

Abstract: Icing will occur when helicopters pass through clouds containing supercooled droplets. The ice accreted on rotor blade affects the safety of helicopter. A numerical simulation method of helicopter rotor icing in forward flight is presented, and the icing characteristics of rotor are studied. The flow field is calculated based on the overlapping grids, and the Eulerian model is applied in the droplet trajectory calculation. The unsteady method is used to calculate rotor flow field and droplet trajectory. The ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Rotorcrafts such as helicopters are operated for a long time at altitudes below 6000 m, where supercooled water droplets may exist in clouds [60]. The airfoil of rotorcraft is generally smaller in size than that of a fixed-wing aircraft, which means water droplets are more likely to impinge since the collection efficiency increases when the leading-edge radius decreases, as reported in [61].…”
Section: Rotor Icingmentioning
confidence: 99%
“…Rotorcrafts such as helicopters are operated for a long time at altitudes below 6000 m, where supercooled water droplets may exist in clouds [60]. The airfoil of rotorcraft is generally smaller in size than that of a fixed-wing aircraft, which means water droplets are more likely to impinge since the collection efficiency increases when the leading-edge radius decreases, as reported in [61].…”
Section: Rotor Icingmentioning
confidence: 99%
“…Although this method is computationally very efficient, it is unable to model the effect of strong rotor wakes associated with multiple rotor blades and their impact on ice accretion on the fuselage. Wang et al [83] reported a recent development in the study of ice accretion on a rotor blade in forward flight with overset grids. Son et al [84] studied ice accretion on wind turbine blades by applying the multiple reference frame approach.…”
Section: Integrated Computational Simulation For Designing the Rotorc...mentioning
confidence: 99%
“…In addition to complex simulation methods for predicting ice accretion on rotors, some simplified methods are also developed [15][16][17][18][19][20][21][22]. Based on the Lewice3D, Narducci [15,16] developed an analysis method to evaluate the ice accretion for a helicopter rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a simple assumption that liquid water flow and mass transfer is mainly affected by the shear stress and the centrifugal force, Zhao [19] studied the ice accretion on rotor in hover considering the centrifugal force into account. Similarly, Wang [20,21] developed an icing model accounting for the influence of centrifugal force. They both obtained some meaningful results and verified the importance of the centrifugal force in the icing process on rotors.…”
Section: Introductionmentioning
confidence: 99%